THE INFLUENCE OF PROVINCIAL CITY ENVIRONMENT ON THE FORMATION OF VALUE RELATION TO HEALTH AMONG CHILDREN AND TEENAGERS - Kondakova, I.V. (Tambov University Review. Series: Humanities, 2016)
The influence of environment on forming valuable relation to the health in younger generation in a provincial city, the main trends in the deterioration of health status of adolescents, key problems of provincial cities are highlighted. The aim of active help the younger generation is to adapt to life, choosing a path of self-realization, overcoming difficulties of life, building life strategies through introduction to a healthy lifestyle. The possibility of achieving a sufficiently high level of motivation of a healthy lifestyle for children and adolescents in a small provincial town on the example of the city of Yelets of the Lipetsk region with the participation of the administration, youth Parliament, activity of youth leaders, residents and using new approaches is discussed. Special attention is paid to the description of steps and measures aimed at forming healthy lifestyle, value attitude to health in terms of a provincial town. The health-saving potential of the city Yelets is marked, opportunities in the context of “Special economic zones of regional level tourist-recreational type” are analyzed. Based on the data obtained in the result of the study, a solution to the problem of forming healthy lifestyle of younger generation through the creation of healthy environment forming value attitude to health is proposed.